1998
DOI: 10.1016/s0378-1127(98)00410-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of organic matter and nutrient return from litterfall in stands of ten tropical tree plantation species

Abstract: We studied the rates and patterns of carbon and nutrient¯uxes in litterfall in ten tropical tree plantation species grown at the USDA Forest Service Arboretum in the Luquillo Experimental Forest, Puerto Rico. The stands were 26-years old and grew under similar climatic and edaphic conditions. Individual plantation species ranked differently in terms of their capacity to return mass and speci®c nutrients to the forest¯oor, and with respect to their ef®ciency of nutrient use. The species that returned the most m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
2
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 22 publications
3
68
2
11
Order By: Relevance
“…In contrast, the 7 % increase in leaf litter N after a decade of fertilization is identical to the increase observed in the first six years (Kaspari et al 2008), suggesting that continued N addition does not further increase leaf litter N. Leaf litter N concentrations varied seasonally, with highest concentrations in the late wet season, but there were no seasonal differences for P. Greater N concentrations in wet season leaf litter were also reported for a nearby forest on Barro Colorado Island (Yavitt et al 2004), as well as in a variety of other tropical forests (e.g., Chuyong et al 2000;Cuevas and Lugo 1998), suggsting that it is a widespread phenomenon. Seasonal variation in leaf litter P appears to be slightly more muted compared to the variation in N, as was also reported for an African forest dominated by ectomycorrhizal trees (Chuyong et al 2000).…”
Section: Seasonal Dynamics Of Soil Organic Mattersupporting
confidence: 55%
See 2 more Smart Citations
“…In contrast, the 7 % increase in leaf litter N after a decade of fertilization is identical to the increase observed in the first six years (Kaspari et al 2008), suggesting that continued N addition does not further increase leaf litter N. Leaf litter N concentrations varied seasonally, with highest concentrations in the late wet season, but there were no seasonal differences for P. Greater N concentrations in wet season leaf litter were also reported for a nearby forest on Barro Colorado Island (Yavitt et al 2004), as well as in a variety of other tropical forests (e.g., Chuyong et al 2000;Cuevas and Lugo 1998), suggsting that it is a widespread phenomenon. Seasonal variation in leaf litter P appears to be slightly more muted compared to the variation in N, as was also reported for an African forest dominated by ectomycorrhizal trees (Chuyong et al 2000).…”
Section: Seasonal Dynamics Of Soil Organic Mattersupporting
confidence: 55%
“…(Cuevas and Lugo 1998). Indeed, only four species out of the hundreds at the site occur in all plots, and those four species vary markedly in their litter nutrient concentrations (Mayor et al 2014).…”
Section: Seasonal Dynamics Of Soil Organic Mattermentioning
confidence: 97%
See 1 more Smart Citation
“…Esta imobilização pode evitar perda por erosão e lixiviação (Cuevas & Lugo, 1998) e contribui para aumentar o teor de nutrientes das suas camadas superficiais, visto que o sistema radicular do eucalipto explora camadas profundas do seu perfil e pode realocar os nutrientes para as camadas superficiais. A intensidade da colheita florestal adotada determina a quantidade de nutrientes exportados do sítio.…”
Section: Quadro 6 Estimativa Do Conteúdo (1) De N P K Ca E Mg Na unclassified
“…It has been suggested that rainfall may have a two-fold influence on litter production as it may induce water stress in dry periods which increases shedding of senescent leaves whereas heavy rainfall at some time of a year force the shedding of non-senescent leaves. This cycle of events provides a nutrient pulse through higher qualities of leaf litter (Cuevas and Lugo, 1998;Johansson 1995;Morrison, 1991;Parker, 1983;Gosz et al, 1976).…”
Section: Seasonal Patterns Of Litterfall Productionmentioning
confidence: 99%